Constitution of a Camelina sativa L. Synthetic Population and Agronomic Comparison between Spring and Winter Cultivation in North Italy - Martina Ghidoli; Sara Frazzini; Stefano De Benedetti; Stefano Sangiorgio; Michela Landoni; Alessio Scarafoni; Luciana Rossi; Roberto Pilu (Agronomy, 2023)
In recent years, the interest in increasingly sustainable agriculture has also turned attention towards new cover crops suitable for use in marginal areas that could enter the food chain as new protein and oil sources or for biodiesel production. In this scenario, Camelina sativa is a perfect crop to study. Camelina is an annual herbaceous plant belonging to the Brassicaceae which is interesting in terms of its oil content, since the seeds contain about 40% oils, with a high level of polyunsaturated fatty acids (30–40% alpha linolenic acid, 15–25% linoleic acid, 15% oleic acid and about 15% eicosenoic acid). It is a hexaploid species (2n = 40, genome size ~782 Mb) characterized by rapid growth, a short life cycle (85–100 days for spring varieties, 190–210 for autumn varieties) and low input cultivation needs. However, its use in feed and food is limited by the presence of glucosinolates (GLS). GLS are sulfur molecules involved in plant defense. In recent years, they have been studied not only as antinutritionals but also for their anti-carcinogenic effects against chronic inflammatory and heart diseases and for their use as natural pesticides. Given the recent interest in camelina and its highly nutritious oil, eight pure lines and a synthetic population were compared in two different growing periods, spring and winter. In this work, the genetic materials were characterized for different phenotypic traits, yields and yield components, and bromatological and glucosinolate content. The results confirmed that in North Italy, camelina has higher yields if cultivated in the autumn–winter period (about 2 t/ha vs. 0.6 t/ha); furthermore, a negative correlation was found between spring and winter yields, indicating that varieties that produce more in winter cultivation produce less in spring cultivation. Moreover, to our knowledge, it is the first work in which a synthetic population of Camelina sativa has been tested and proved to be a valid solution for use in various environments both for its adaptability and for the low content of glucosinolates (about 17 mmol/kg).